1991
DOI: 10.1161/01.hyp.18.5.565
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine, the heart, and coronary circulation.

Abstract: Adenosine is known to regulate myocardial and coronary circulatory functions. Adenosine not only dilates coronary vessels, but attenuates 0-adrenergic receptor-mediated increases in myocardial contractility and depresses both sinoatrial and atrioventricular node activities. The effects of adenosine are mediated by two distinct receptors (i.e., A, and A 2 receptors). A, adenosine receptors, located in atrial and ventricular myocardium and sinoatrial/atrioventricular nodes, are responsible for inhibition of aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
114
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(118 citation statements)
references
References 156 publications
(67 reference statements)
0
114
0
Order By: Relevance
“…Interestingly, catecholamine, angiotensin, aldosterone, and cytokines are known to be involved in the pathophysiology of CHF (2)(3)(4)(5), as evidenced by the fact that β-adrenoceptor antagonists, angiotensin-converting enzyme (ACE) inhibitors, and aldosterone receptor antagonists are widely accepted as drugs for CHF (6,7). Adenosine has biological effects on various tissues (8)(9)(10). Since several lines of evidence (9,10) support the idea that adenosine is cardioprotective against deleterious sequels in CHF as well as ischemic heart disease, it is intriguing and important to analyze the adenosine receptor-or adenosine metabolismrelated genes using DNA microarray analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, catecholamine, angiotensin, aldosterone, and cytokines are known to be involved in the pathophysiology of CHF (2)(3)(4)(5), as evidenced by the fact that β-adrenoceptor antagonists, angiotensin-converting enzyme (ACE) inhibitors, and aldosterone receptor antagonists are widely accepted as drugs for CHF (6,7). Adenosine has biological effects on various tissues (8)(9)(10). Since several lines of evidence (9,10) support the idea that adenosine is cardioprotective against deleterious sequels in CHF as well as ischemic heart disease, it is intriguing and important to analyze the adenosine receptor-or adenosine metabolismrelated genes using DNA microarray analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine has biological effects on various tissues (8)(9)(10). Since several lines of evidence (9,10) support the idea that adenosine is cardioprotective against deleterious sequels in CHF as well as ischemic heart disease, it is intriguing and important to analyze the adenosine receptor-or adenosine metabolismrelated genes using DNA microarray analysis. Adenosine is known to be an endogenous nucleoside acting as a cardioprotective substance that modulates numerous physiological processes, including the regulation of coronary blood flow (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The major actions of ADO are 1) vasodilation and afterload reduction through a decrease of peripheral resistance, 2) increase of both cardiac output and stroke volume without inducing tachycardia and 3) increase of CBF and decrease of cardiac oxygen consumption. 13 These hemodynamic effects appear to be mediated by ADO receptors, 14,15 with the major ADO receptors designated as A1 and A2. A1 receptors mainly mediate inhibition of norepinephrine release, 16 inhibition of excessive myocardial contraction induced by beta-stimulation 17,18 and delay of stimulation conduction velocity, 14 all actions which reduce myocardial oxygen demand.…”
Section: Discussionmentioning
confidence: 99%
“…22 Therefore, it is possible that the antiarrhythmic efficacy of dipyridamole is due to improved coronary flow. However, in the present study, intracoronary nitroglycerin showed little effect toward prevention of reperfusion arrhythmias.…”
Section: Antiarrhythmic Action Of Adenosine and Dipyridamolementioning
confidence: 99%